Effect of cooling temperature on microstructure and mechanical properties of Nb microalloyed hot-rolled rebar - Yafei Jiang; Shangjun Gu; Jie Wang; Fulong Wei; Zeyun Zeng; Tianyou Wang; Hongfeng Shi; Changrong Li; Zhiying Li (Journal of Materials Research and Technology)
In this study, the Gleeble-3800 thermal simulation tester was used to simulate various cooling temperature processes for two groups of rebar. Then, the microstructure, precipitation, and mechanical properties of the rebars were characterized using SEM (scanning electron microscopy), EBSD (electron backscatter diffraction), HRTEM (high resolution transmission electron microscopy), and MST810 (universal tensile testing machine). The effect of cooling temperature on the microstructure and mechanical properties was systematically investigated. The results showed that reducing the cooling temperature from 750 °C to 600 °C decreased the ferrite grain size in 0.032 wt % Nb rebar to 7.03 ± 1.5 μm, compared to the 0 wt% Nb rebar. In addition, the pearlite lamellar spacing was refined to 0.103 ± 0.5 μm, and the average particle size of elliptical Nb-rich composite carbides was 9 nm. The tensile strength and yield strength reached 795 ± 9 MPa and 638 ± 8 MPa, respectively, with an elongation after fracture of 17.78 ± 1.0 %. The fracture surface exhibited a dimple morphology.